PEG TUBE INSERTION IN NEURODEGENERATIVE DISEASE. Issue 12 (15th November 2016) - Sarkar, Pamela; Cole, Alice; Scolding, Neil; Rice, Claire
Abstract : Background: Percutaneous endoscopic gastrostomy (PEG) tube insertion is a well-established method of long term enteral feeding. Although artificial feeding in the context of neurodegenerative disease presents particular challenges, relatively little is known regarding the safety and utility of PEG tube insertion in these patients with the notable exceptions of dementia, stroke and motor neurone disease. Aims and Method: We sought to determine the safety and utility of PEG feeding in the context of neurodegenerative disease in a single neurosciences centre and to complete a literature review with the aim of identifying whether particular factors need to be taken into consideration to improve safety and outcome. Patients with a diagnosis of stroke or dementia were not included. Results: Short term mortality and morbidity associated with PEG tube insertion were significant. Age greater than 75 years was associated with poor outcome and there was a trend towards adverse outcome in those with low serum albumin. Conclusion: This study highlights the relatively high risk of PEG tube placement in patients with neurodegenerative disease. We present a number of points for consideration with the aim of improving the outcome in this particularly vulnerable group of patients.